2014
DOI: 10.1371/journal.pone.0106400
|View full text |Cite
|
Sign up to set email alerts
|

Faces in a Crowd: High Socially Anxious Individuals Estimate that More People Are Looking at Them than Low Socially Anxious Individuals

Abstract: BackgroundPeople with social anxiety disorder are afraid of being scrutinized by others and often feel that they are the excessive focus of other people's attention. This study investigated whether, when compared to low socially anxious individuals, high socially anxious individuals overestimate the proportion of people in a crowd who are observing them. It was hypothesized that any potential overestimation would be modulated by self-focused attention.MethodForty-eight high and 48 low socially anxious particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 21 publications
(27 reference statements)
3
9
2
Order By: Relevance
“…In contrast to the Bolt et al (2014) study, we did not observe a significant effect of Social Anxiety Group in the Faces Task ( β = 1.06, SE = 1.18, t (9144) = .89, p = .372), although HSA participants ( M = 41.80, SD = 6.50) tended to give higher estimates than LSA participants ( M = 40.71, SD = 5.89). When we compared the Bolt et al (2014) sample with our own we found that the mean differences on measures of social anxiety between high and low socially anxious groups were substantially smaller in our study (only 56% of the Bolt et al difference on APPQSP, 59% on SCS, and 44% on SFAS).…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to the Bolt et al (2014) study, we did not observe a significant effect of Social Anxiety Group in the Faces Task ( β = 1.06, SE = 1.18, t (9144) = .89, p = .372), although HSA participants ( M = 41.80, SD = 6.50) tended to give higher estimates than LSA participants ( M = 40.71, SD = 5.89). When we compared the Bolt et al (2014) sample with our own we found that the mean differences on measures of social anxiety between high and low socially anxious groups were substantially smaller in our study (only 56% of the Bolt et al difference on APPQSP, 59% on SCS, and 44% on SFAS).…”
Section: Resultscontrasting
confidence: 99%
“…For each trial, the fixation cross was presented for 1000ms, followed by the picture matrix for 2750ms. This was enough time for participants to scan the faces, but not long enough to count them (Bolt et al, 2014). Next, participants gave their estimate on an analogue scale (Nobody (0%) – Everybody (100%)), with no time limit.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations